The Effect of Financial Technology and Self-Control on Impulsive Buying: The Moderating Role of Income - Mufassiro, Ani; Zaki, Achmad; Mustaqim, M.; Putrihadiningrum, Devika Cherly (Faculty of Economics dan Business, Atma Jaya Makassar University, 2025)
This research seeks to examine the influence of financial technology usage and self-control on impulsive buying behavior, with income serving as a moderating variable. A quantitative approach with an explanatory method is employed in this study. A sample of 96 respondents was obtained through accidental sampling technique, namely Belikopi consumers in Sidoarjo who actively use fintech services in transactions. The data obtained was analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0 software. The results showed that the use of financial technology has a positive and significant effect on impulsive buying. In contrast, self-control does not have a significant effect on this behaviour. Moreover, income has been found to moderate and diminish the impact of financial technology on impulsive buying behavior. In contrast, income strengthens the effect of self-control on impulsive buying. This finding implies that income plays an important role in weakening or strengthening technological and psychological influences on impulsive consumption behaviour.